2017
DOI: 10.3945/ajcn.116.139758
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of urinary biomarkers in multiple 24-h urine samples

Abstract: Background: Limited knowledge regarding the reproducibility of biomarkers in 24-h urine samples has hindered the collection and use of the samples in epidemiologic studies. Objective: We aimed to evaluate the reproducibility of various markers in repeat 24-h urine samples. Design: We calculated intraclass correlation coefficients (ICCs) of biomarkers measured in 24-h urine samples that were collected in 3168 participants in the NHS (Nurses' Health Study), NHSII (Nurses' Health Study II), and Health Professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 38 publications
5
58
0
Order By: Relevance
“…This may happen if noise is the major factor affecting variability, either because extrinsic factors (e.g., episodes of pollution) affect the biomarker in a random fashion or because the individuals in the cohort are so similar that variations within and between individuals are the same. The majority of the ICCs are actually well above the level previously termed "fair," as a rule of thumb (6), and reliability measurements in the study by Sun et al (5) actually confirm the previous empirical ICC threshold. This result is expected from a large number of recent studies in metabolomics that indicate short excretion half-lives of most food-derived compounds (7).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…This may happen if noise is the major factor affecting variability, either because extrinsic factors (e.g., episodes of pollution) affect the biomarker in a random fashion or because the individuals in the cohort are so similar that variations within and between individuals are the same. The majority of the ICCs are actually well above the level previously termed "fair," as a rule of thumb (6), and reliability measurements in the study by Sun et al (5) actually confirm the previous empirical ICC threshold. This result is expected from a large number of recent studies in metabolomics that indicate short excretion half-lives of most food-derived compounds (7).…”
supporting
confidence: 76%
“…The validity of a biomarker for intake estimates also depends on how representative an analytic sample is for average exposures, the kinetics of the analyte in the body, and how variable the biomarker is within and between individuals (4). There are comparatively few data on these issues, and the article by Sun et al (5) in this issue of the Journal provides a large amount of new information and guidance to the community with regard to biomarkers measured in urine. The study compares repeated measurements of common electrolytes, nutrients, phenolics, and contaminants in 3 large cohorts of American health professionals to outline the effects of repetition number, sampling intervals, and anthropometric and nutritional variables.…”
mentioning
confidence: 99%
“…Day-to-day variability in dietary sodium and potassium intake could have influenced our renin and aldosterone results, an issue that is further compounded by the fact that sodium and potassium phenotyping occurred years before the renin and aldosterone phenotyping. However, the sodium and potassium balances were comparable across renin phenotypes (Supplemental Table 3), and large cohort studies have shown intra-individual correlation and reasonable reproducibility in these metrics over 1–3 years of follow-up(40, 41). More importantly, the aforementioned limitation does not degrade the validity of our observational findings which are supported by physiologic principles: 1) the decoupling of elevated aldosterone levels and suppression of renin that associated with the highest risk for incident hypertension (Figure 1A) cannot be explained by dietary sodium balance, rather can only be explained as an autonomous or renin-independent aldosteronism; 2) conversely, renin-dependent aldosterone secretion (Figure 1C) cannot be ascribed to autonomous aldosterone secretion since renin was not suppressed, and was therefore presumptively physiologic.…”
Section: Discussionmentioning
confidence: 91%
“…Although this resulted in comparisons of aldosteronism phenotypes with measures of MR activity across examinations, we used these comparisons as a cross-sectional and mechanistic validation to our longitudinal findings, and in this regard, our two analyses were complimentary and consistent. It should be noted that all participants were normotensive and untreated at examination 2 or 3 (when aldosterone and PRA were measured), and therefore it is likely that these phenotypic characteristics were stable and representative of each participant’s renin and aldosterone phenotype(40, 41). Second, as discussed earlier, measures of renin and aldosterone were performed on ad libitum dietary sodium intake.…”
Section: Discussionmentioning
confidence: 99%
“…While the size of a clinically significant reduction is unknown, the KSS study showed the mean 24-hour urinary phosphorus excretion at baseline to range from 738 mg/day (SD = 221) to 1032 mg/day (SD = 300) [41]. Conservatively assuming the larger SD, with a sample of 240 (60/group), using a 2-tailed two sample t -test and a significance level α = 0.008, we can detect differences from baseline in urinary phosphorus excretion as small as 194 mg/day with 80% power.…”
Section: Methodsmentioning
confidence: 99%